Analisis Kinerja Dehydrator Berbahan Bakar Briket Kayu dalam Pengeringan Daun Salam (Eugenia polyantha) - Rizkia Rahmawati; Muhammad Nasiruddin; Ahmad Egy Mursalin; Mahmud Yasin; Muji Juherwin (Jurnal Engine: Energi, Manufaktur, dan Material, 2025)
Drying is an essential method for preserving food materials to extend shelf life and maintain product quality. This study aims to analyze the performance of a wood briquette-fueled dehydrator in drying bay leaves (Eugenia polyantha). The research focuses on the effect of the quantity of wood briquettes on temperature stability, drying duration, and product quality. The results indicate that the amount of wood briquettes significantly affects the maximum temperature achieved, with the highest temperature recorded at 70.69°C over 8 hours. The wood briquette-fueled dehydrator effectively reduced the moisture content of bay leaves by more than 60%, producing a dried texture suitable for long-term storage, particularly within a drying duration of 6–8 hours at an optimal temperature range of 40–60°C. Furthermore, the use of wood briquettes as a renewable energy source provided even heat distribution and reduced dependence on fossil fuels, making it an energy-efficient and environmentally friendly solution.